Weight gain, serum leptin and triglyceride levels in patients with schizophrenia on antipsychotic treatment with quetiapine, olanzapine and haloperidol - Atmaca, M; Kuloglu, M; Tezcan, E; Gecici, O; Ustundag, B (Elsevier Science Bv, 2003)
[Abstract Not Available]
Keywords: Body-Weight; Food-Intake; Serotonin